2006
DOI: 10.1186/1477-7525-4-88
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the short version of the Psychological General Well-Being Index (PGWB-S)

Abstract: Background: The PGWBI is a 22-item health-related Quality of Life (HRQoL) questionnaire developed in US which produces a self-perceived evaluation of psychological well-being expressed by a summary score. The PGWBI has been validated and used in many countries on large samples of the general population and on specific patient groups. Recently a study was carried out in Italy to reduce the number of items of the original questionnaire, yielding the creation of a shorter validated version of the questionnaire (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
177
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(194 citation statements)
references
References 24 publications
10
177
2
5
Order By: Relevance
“…In accordance with the stratification of the PGWBI score, 32.9% of the population had a positive well-being, 27.1% distress absence, 37.1% moderate distress and 2.9% severe distress. Compared to the Italian reference population aged between 65 and 74 years [30], COPD patients had a comparable PGWBI total score, although they showed significantly worse scores in vitality (p < 0.0001) and general health (p < 0.0424). Pearson correlation showed that the total PGWBI score was not correlated with FEV 1 (r = 0.162; p = 0.060) and Charlson weighted index of comorbidity (r = –0.67; p = 0.434), while a significant correlation was found with the MRC score (Spearman correlation r = –0.466; p = 0.0001; fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the stratification of the PGWBI score, 32.9% of the population had a positive well-being, 27.1% distress absence, 37.1% moderate distress and 2.9% severe distress. Compared to the Italian reference population aged between 65 and 74 years [30], COPD patients had a comparable PGWBI total score, although they showed significantly worse scores in vitality (p < 0.0001) and general health (p < 0.0424). Pearson correlation showed that the total PGWBI score was not correlated with FEV 1 (r = 0.162; p = 0.060) and Charlson weighted index of comorbidity (r = –0.67; p = 0.434), while a significant correlation was found with the MRC score (Spearman correlation r = –0.466; p = 0.0001; fig.…”
Section: Resultsmentioning
confidence: 99%
“…The scores for all domains are summarized in a global score, which reaches a maximum of 110 points, representing the best achievable well-being. In accordance with questionnaire developers, the results can also be grouped according to the well-being level into: positive well-being (score ≥96), no distress (≥73 and ≤95), moderate distress (≥60 and ≤72) and severe distress (<60) [30]. …”
Section: Methodsmentioning
confidence: 99%
“…It is quite clear that health status is one the major determinants of a subjective sense of well-being. In a survey carried out in Italy in 2000, health status (expressed as the number of concomitant diseases) actually emerged as the top determinant of perceived well-being, followed by income and age (Grossi et al 2006). In fact, considering that the average PGWBI index in a general population sits around a score of 78, it turns out that people without any disease show average values around 82, whereas to subgroups with 1, 2, 3, 4 or 5 or more diseases correspond decreasing average scores (79, 78, 77, 73, 66, 56 respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Subjective measures that are person-centred have long been established empirically in health sciences as appropriate ways to define one's quality of life, instead of externally defined objective indicators (Diener et al 1985, Ruta et al 1994. Across fields, well-being as concept has been used for the creation of cross-country data sets (Deaton 2007, Diener et al 2010, national assessments and indexes (Grossi et al 2006, Lind 2014, Topp et al 2015, and localized contextualized studies (Adelson 2000, Donatuto et al 2011. A prominent example is Narayan et al's (2000) "Voices of the Poor" research, undertaken under the World Bank's commission, which reviewed participatory poverty studies conducted in the 1990s and conducted a series of new studies across 23 countries in which poor people discussed their perceptions of a good life and a bad life.…”
Section: Operationalizing Well-being As a Conceptmentioning
confidence: 99%